Timeline - Done, Richard; Maguire, Jeff.; Nolfi, George; Paramount Pictures Corporation; Mutual Film Company; Cobalt Media Group; Donner's Company (Firm).; Artists Production Group (Firm). ([United States] Paramount Pictures ; distributed in the Philippines by MagnaVision, 2004)
A group of present-day archeology students are stunned to discover a handwritten plea for help dated April 2, 1357...from their own professor. He's been blasted back in time to the 14th century. To rescue him, they must travel back and survive one of the most violent battles in world history--and make it back to the 21st century alive.
Based on the novel by Michael Crichton.
Director of photography, Caleb Deschanel ; editor, Richard Marks ; music, Brian Tyler ; costume designer, Jenny Beavan ; production designer, Daniel T. Dorrance ; executive producers, Michael Ovitz, Gary Levinsohn, Don Granger.
Paul Walker, Frances O'Connor, Gerard Butler, Billy Connolly, David Thewlis, Anna Friel, Neal McDonough, Matt Craven, Ethan Embry.
MPAA rating: PG-13, for intense battle scenes and brief language.
VCD
Keywords: Time travel -- Drama; Historians -- Drama; Quantum theory -- Drama; France -- History -- 14th century -- Drama